Inoculum Rate Effects on the Soybean Symbiosis in New or Old Fields under Tropical Conditions. (1st May 2017) - Hungria, Mariangela; Araujo, Ricardo Silva; Silva Júnior, Elson Barbosa; Zilli, Jerri Édson
Abstract : Core Ideas: Inoculum rate with elite strains is critical to achieve the benefits of biological N2 fixation. The minimum rate of 1.2 × 10 6 cells of Bradyrhizobium seed −1 was determined to benefit biological N2 fixation. Soybean can highly benefit from biological N2 fixation. Some sites required 2.4 × 10 6 cells seed −1 and could respond to higher rates. Soybean [ Glycine max (L.) Merr.] can highly benefit from inoculation with elite strains of Bradyrhizobium, selected for high capacity of N2 fixation. However, to achieve the benefits, the strains must be capable of effectively nodulate the host, and inoculum rate may be critical, especially under stressing tropical environmental conditions. We performed 10 field experiments, in four crop seasons and four Brazilian states, including soils without and with established populations of soybean bradyrhizobia, to investigate the effects of inoculum rates, consisting of zero, 0.6 × 10 6, 1.2 × 10 6, and 2.4 × 10 6 colony forming units (CFU) per seed. Nodule number and dry weight were evaluated at early flowering and grain yield and N content in grains at the physiological maturity. Satisfactory nodulation and grain yields were obtained with 1.2 × 10 6 CFU seed −1 . However, there were sites with and without established population of bradyrhizobia where maximum nodulation and/or yields were achieved with inoculum rate of 2.4 × 10 6 CFU seed −1, and that could require even higher rates. Therefore, we suggest the adoption of the minimum inoculum rate of 1.2 × 10 6 cells of Bradyrhizobium seed −1 for soybean planting in the tropics, to achieve maximum contribution of biological N2 fixation.